ALUVIÃO IN FUNCHAL, MADEIRA ISLAND: HISTORIC ASPECTS, CONCEPTS AND POTENCIAL DAMAGE INDEX - Freitas, Hugo Filipe Barreto Ferreira de; Goerl, Roberto Fabris; Michel, Gean Paulo (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.971, 2020)
The district of Funchal, located on Madeira Island, is often affected by a process known regionally as Aluvião. This process has been recorded since 1600, however the event of 2010 was the most important in terms of financial loss and damage. The Aluvião has, at the same time, characteristics of debris flow, hyperconcentrated flow and floods. This paper analyzed the concept of Aluvião and its characteristics, as well as proposed a potential damage index that takes into account the urbanization of the basins and their susceptibility to Aluvião. Google Earth Pro (GE) imagery was used to map 2010 landslide scars and classify the basins in terms of susceptibility. The Enhanced Vegetation Index 2 (EVI2) was used as a proxy for urbanization and its temporal evolution was analyzed. Through the literature review, it was noted that the Aluvião is commonly treated as flood, followed by flash flood and landslide. Based on the GE images, 123 scars were mapped and the basins classified in terms of susceptibility. The EVI2 presented typical values ​​for urbanization, which allowed to evaluate its temporal and spatial evolution. Based on the potential damage index, the basins was classified, indicating the most likely to be affected by the Aluvião. In addition, the index can be used for disaster management and guide the urbanization to the less susceptible basin. Finally, the methodology proved feasible and can be applied in any basin where there are spatial information about landslides and urbanization.